2000
DOI: 10.1016/s0736-5748(00)00024-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of calbindin‐D28k and parvalbumin during development of rat's basolateral amygdaloid complex

Abstract: Parvalbumin and calbindin-D28k are calcium-binding proteins, which are considered to be markers for certain populations of GABAergic neurons. Their correct development in the basolateral amygdaloid complex is critical for the proper emotional functioning in adult live of human and animals. Therefore, in this paper we describe the pattern of the morphological differentiation and distribution of immunoreactive elements of the parvalbumin and calbindin-D28k in this complex on the basis of immunohistochemically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 70 publications
5
65
1
Order By: Relevance
“…However, the current study is the first to demonstrate directly the age bias in the effects of stress on GABAergic regulation of LAT neurons. In rats, BLA parvalbumin-positive interneurons reach maturity at~PND 30 (Berdel and Morys, 2000;Legaz et al, 2005;Davila et al, 2008), which overlapped with the start of our repeated restraint protocol during adolescence. Repeated stress may stunt the final phases of prepubertal GABAergic development leading to greater impact of stress on GABAergic systems in adolescence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the current study is the first to demonstrate directly the age bias in the effects of stress on GABAergic regulation of LAT neurons. In rats, BLA parvalbumin-positive interneurons reach maturity at~PND 30 (Berdel and Morys, 2000;Legaz et al, 2005;Davila et al, 2008), which overlapped with the start of our repeated restraint protocol during adolescence. Repeated stress may stunt the final phases of prepubertal GABAergic development leading to greater impact of stress on GABAergic systems in adolescence.…”
Section: Discussionmentioning
confidence: 91%
“…The GABAergic system in the BLA is still developing during the first several weeks postnatal. In rodents, the GABAergic interneuron network and basic GABAergic IPSC kinetics do not reach maturity until~PND 14-28 (Berdel and Morys, 2000;Legaz et al, 2005;Olmos et al, 2005;Davila et al, 2008;Ehrlich et al, 2013). GABA also appears to exert differences in inhibitory regulation at later ages.…”
Section: Discussionmentioning
confidence: 99%
“…While the amygdala continues to develop through adolescence, nuclei are distinct by P7 and responsive to olfactory information during the early neonatal period (Schwob et al, 1984;Berdel et al, 1997;Morys et al, 1999;Nair and Gonzalez-Lima, 1999;Berdel and Morys, 2000;Bouwmeester et al, 2002;Wilson, 2003). However, at this age, minimal connections exist between the amygdala and other brain areas considered important in fear conditioning, such as the prefrontal cortex and hippocampus (Nair and Gonzalez-Lima, 1999;Bouwmeester et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…2, available at www.jneurosci.org as supplemental material). A recent study has suggested that parvalbumin-positive interneurons in the rat BLA undergo significant developmental changes in their distribution and morphology between the ages of postnatal day 21 (P21) and P30 (Berdel and Morys, 2000). Our studies have been limited to animals aged P16 -P25 with most experiments being done on animals aged around P16 -P18.…”
Section: Identification and Classification Of Pv؉ Interneuronsmentioning
confidence: 99%